Practical modern SCADA protocols : DNP3, 60870.5 and Related Systems - Clarke, Gordon R. (Colección de libros electrónicos de ULoyola, 2004)
SCADA (Supervisory Control and Data Acquisition) systems are at the heart of the modern industrial enterprise ranging from mining plants, water and electrical utility installations to oil and gas plants. In a market that is crowded with high-level monographs and reference guides, more practical information for professional engineers is required.